Optimal power flow considering line loss - Banna, Hasanul; Ehsan, Md. Samiul; Hussain, Md. Samiul (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.